Peripheral pharmaceutical intervention program for the prevention of iron deficiency anemia in children - Alcalá pimentel, María Antonieta (2023)
Objective: To identify how the implementation of a peripheral pharmaceutical intervention program influences the prevention of anemia in children from 0 to 5 years of age.Materials and methods: A quantitative, descriptive and comparative study was conducted with a purposive non-probability sampling. The study population consisted of 40 children and the sample included 28 children from 0 to 5 yearsof age, of both sexes, living in the Carlos Manuel Cox shanty town, located in the district of Ancón, province of Lima, Peru. Hematological tests were performed to measure the hemoglobin level in the children, and questionnaires wereadministered to their caregivers or parents. An awareness program on anemia, parasitosis, nutritious food, good hygienepractices, medical control, and medical and pharmacological treatment was undertaken. A Likert scale was used to determine the prevention of iron deficiency anemia. For blood analysis, a microhematocrit test was performed to measure the hemoglobin levels, prior to the awareness of anemia. The sampling was carried out by a medical technologist together with the researchers. Data processing was conducted using IBM SPSS Statistics V25.0 and Microsoft Excel programs. Correlations between variables were determined using Pearson’s correlation coefficient. Results:Concerning the results of knowledge about anemia, a mean of 7.6 and a standard deviation of 2.5 were found in the pretest, and a mean of 18.0 and a standard deviation of 0.0 were found in the posttest, thus there was no increase in knowledge. Conclusions: The pharmaceutical intervention program positively influences the knowledge of mothers about the prevention of iron deficiency anemia in their children.